Effect of Geopolitical Risk on Bitcoin’s Price From 2016-2021: Comparative Analysis Pre-During Covid-19 Pandemic Period - Bangun, Mey Frida Yosefa; Warganegara, Dezie Leonarda (Innovation Journal of Social Sciences and Economic Review, 2023)
This study investigates the effects of geopolitical risks (GPR) and its component indexes on Bitcoin’s price from January 1, 2016, to December 31, 2021, with a specific focus on how the COVID-19 pandemic influenced the relationship between GPR and Bitcoin’s price. We employed quantitative data analysis techniques, including Ordinary Least Squares (OLS) and Quantile Regression (QQ), to analyze the data over the specified period. The study covers a comprehensive dataset from January 1, 2016, to December 31, 2021, capturing both pre- and during-COVID-19 pandemic phases. The OLS estimations show that Bitcoin’s price is both positively and negatively related to GPR and its components, although these relationships were statistically insignificant before and during the COVID-19 pandemic. However, Quantile Regression results indicate that the effects of GPR and its component GPRA on Bitcoin’s price are positive and statistically significant at the higher quantiles, particularly during the COVID-19 pandemic. The study concludes that while the direct effects of geopolitical risks on Bitcoin’s price may not be statistically significant across the board, significant positive impacts are observed at higher price quantiles, especially during periods of heightened geopolitical uncertainty, such as the COVID-19 pandemic. The findings suggest that Bitcoin could serve as a hedge against geopolitical risks, particularly in times of extreme global uncertainty. This research provides valuable insights for investors considering Bitcoin as a potential investment during economic recessions or periods of geopolitical instability. Future research should explore a broader scope of variables and methodologies to further understand the complex dynamics between geopolitical risks and cryptocurrency markets.